61.8k views
1 vote
4(a2-b2)2-8ab(a2-b2)-5a2b2 please help me​

2 Answers

2 votes

Answer:
4a^4+4b^4-8a^3b+8ab^3-13a^2b^2

Explanation:


4(a^2-b^2)^2-8ab(a^2-b^2)-5a^2b^2

First, solve the square binomial.


4((a^2)^2-2(a^2)(b^2)+(b^2)^2)-8ab(a^2-b^2)-5a^2b^2


4(a^4-2a^2b^2+b^4)-8ab(a^2-b^2)-5a^2b^2

Now, distribute the 4 and 8ab respectively.


4a^4-8a^2b^2+4b^4-8a^3b+8ab^3-5a^2b^2

Combine like terms. (I'll group them so that you can see them more clearly)


4a^4+4b^4-8a^3b+8ab^3+(-8a^2b^2-5a^2b^2)


4a^4+4b^4-8a^3b+8ab^3+(-13a^2b^2)


4a^4+4b^4-8a^3b+8ab^3-13a^2b^2

User Qikun
by
5.8k points
0 votes

Answer:

(2a²-2b²+a²b²)(2a²-2b²-5a²b²)

Explanation:

4(a²-b²)²-8ab(a²-b²)-5a²b²

Let's replace 2(a²-b²)= m and a²b²=n for simplicity

then we have

  • m²-4mn-5n²
  • = m²-4mn+4n²-4n²-5n²
  • = (m-2n)²- 9n²
  • = (m-2n)²- (3n)²
  • = (m-2n+3n)(m-2n-3n)
  • = (m+n)(m-5n)

Now we can replace m and n with initial values:

  • (m+n)(m-5n)=
  • = (2(a²-b²)+a²b²)(2(a²-b²)- 5a²b²)
  • = (2a²-2b²+a²b²)(2a²-2b²-5a²b²)
User Ian Elliott
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.